2019
DOI: 10.1038/s41467-019-12930-y
|View full text |Cite
|
Sign up to set email alerts
|

MT1-MMP directs force-producing proteolytic contacts that drive tumor cell invasion

Abstract: Unraveling the mechanisms that govern the formation and function of invadopodia is essential towards the prevention of cancer spread. Here, we characterize the ultrastructural organization, dynamics and mechanical properties of collagenotytic invadopodia forming at the interface between breast cancer cells and a physiologic fibrillary type I collagen matrix. Our study highlights an uncovered role for MT1-MMP in directing invadopodia assembly independent of its proteolytic activity. Electron microscopy analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
111
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(124 citation statements)
references
References 63 publications
6
111
2
1
Order By: Relevance
“…He showed that the formation of matrix-degrading invadopodia is triggered by contacts between surrounding collagen fibres and MT1-MMP exposed at the cellular surface. Interestingly, DDR1 repressed this process (Ferrari et al, 2019). Charles Saby (University of Reims, Reims, France) presented evidence of an inverse correlation between MT1-MMP and DDR1 in invasive basal-like breast cancer.…”
Section: Ddrs In Cancermentioning
confidence: 99%
“…He showed that the formation of matrix-degrading invadopodia is triggered by contacts between surrounding collagen fibres and MT1-MMP exposed at the cellular surface. Interestingly, DDR1 repressed this process (Ferrari et al, 2019). Charles Saby (University of Reims, Reims, France) presented evidence of an inverse correlation between MT1-MMP and DDR1 in invasive basal-like breast cancer.…”
Section: Ddrs In Cancermentioning
confidence: 99%
“…Three-dimensional cell culture models in combination with advanced microscopic techniques allow a detailed visualization of cells invading in environments mimicking the tumor stromal architecture. For instance, breast cancer cells embedded in fibrillar type I collagen elaborate TKS5-positive curved invadopodia along collagen fibers, which display membrane type I metalloproteinase (MT1-MMP) dependent collagenolytic activity [ 54 ]. MT1-MMP proteolysis opens pores in the collagen matrix, which are further widened by actin polymerization-based forces at expanding circular invadopodia [ 54 ].…”
Section: Cellular Mechanisms Of Pdac Invasionmentioning
confidence: 99%
“…For instance, breast cancer cells embedded in fibrillar type I collagen elaborate TKS5-positive curved invadopodia along collagen fibers, which display membrane type I metalloproteinase (MT1-MMP) dependent collagenolytic activity [ 54 ]. MT1-MMP proteolysis opens pores in the collagen matrix, which are further widened by actin polymerization-based forces at expanding circular invadopodia [ 54 ]. This study indicates that invadopodia facilitate invasion through collagen fibers by using a combination of proteolytic and mechanical means.…”
Section: Cellular Mechanisms Of Pdac Invasionmentioning
confidence: 99%
“…MT1-MMP has a profound relevance in angiogenesis and cancer [10,11]. Since evidence showed a strong correlation between MT1-MMP expression levels and tumour invasiveness [12][13][14][15][16], a lot of research has been focused in unravelling the mechanisms that control its activity. Due to the variability of substrates cleaved by this enzyme and the low expression levels needed for detecting a significant effect, MT1-MMP activity has to be tightly regulated.…”
Section: Introductionmentioning
confidence: 99%